Analisis Implementasi Prinsip-Prinsip Good University Governance Dalam Pengelolaan Aset Tetap : Studi Kasus Pada Universitas Muhammadiyah Sukabumi - Yuniarti, Elin; Gatot Wahyu Nugroho (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The method used is a qualitative research method with a descriptive approach. The data collection techniques used were observation, interviews and documentation, then the data analysis techniques used were data reduction, data presentation and finally drawing a conclusion. The principles of good university governance in this study use five aspects, namely transparency, accountability, responsibility, independence and fairness. The results of the research conducted show that (1) the process of managing fixed assets at the Muhammadiyah University of Sukabumi at this time is that there are still some problems found, (2) the implementation of the principles of good university governance at the Muhammadiyah University of Sukabumi is not well implemented, this is evident from the non-fulfillment of two principles of good university governance, namely transparency and responsibility, (3) how to implement good university governance in the management of fixed assets at the Muhammadiyah University of Sukabumi, namely the existence of information technology system assistance, the existence of a fixed asset management manual from PP Muhammadiyah (2) the obstacles are limited human resources, time, and lack of participation of fixed asset managers, how to overcome this by making an action plan table.